DEVELOPMENT OF INQUIRY SCIENCE ISSUES-BASED STUDENT WORKSHEET TO ADVANCE PRACTICAL SKILL AND ENVIRONMENTAL ATTITUDE IN A SEVENTH GRADE HIGH SCHOOL STUDENTS - Hirmampuni Adinda Putri; Eko Widodo; Purwanti Widhy Hastuti (Journal of Science Education Research, 2017)
The aims of this research were to (1) develop inquiry science issues-based student worksheet based which is feasible to advance students ' practical skills and environmental attitude, (2) know the students ' responses towards inquiry science issues-based student worksheet, (3) know the advancement of students ' practical skills after using the developed inquiry science issues-based student worksheet and (4) know the advancement of students ' environmental attitude after using the developed inquiry science issues-based student worksheet. Research of the model that is being conducted is 4 d model (define, design, develop, and disseminate). Data were collected using validation form, student response student worksheet, towards a questionnaire inquiry science issues observation form, practical skill observation form, pretest-posttest of practical skill, and environmental attitude questionnaire. The data were analyzed four scale analysis, percentage for practical skill and science issues inquiry learning, N-gain score, and paired sample t-test. According to results, (1) the color worksheet was feasible to advance students ' practical skills and environmental attitude; (2) Students ' responses to the worksheets developed were found very good (A); (3) The average score of practical skills after using the color worksheet was 77.87%. Gains were found between practical skill pre and post test scores. The value of the gains were 0.65, categorized as medium gains. Paired sample t-test indicated that there was significant advancement of students ' practical skills after using the developed student worksheet with the Sig. value was reported to be 0.000; (4) The average score of environmental attitude after using the color worksheet was 87.58%. The value of the gains were 0.65, categorized as medium gains. Paired sample t-test indicated that there was significant advancement of students ' environmental attitude after using the developed student worksheet with the Sig. value was reported to be 0.000.